Mission statements of universities worldwide - Text mining and visualization (2018)
Purpose: To conduct a transnational study of universities' mission statements (MS) through content analysis by identifying characteristics related to language (e.g., number of words, the most and least frequently used words) and if those characteristics are related to universities' location, size, focus, research output, age band, and status. Design/methodology: Content analysis of 248 MS from universities worldwide using Voyant Tools. Findings: The main results show: (1) a necessity for self-awareness by the universities; (2) an overall emphasis on society and students, as stakeholders; (3) there were no discernible similarities in keywords used between firms and universities; (4) MS tend to be longer in universities from Asia and shorter from Europe; (5) the absence of quantitative elementsinto MS (e.g. number of new students enrolled); (6) small universities prioritized knowledge over research; (7) the youngest universities tend to use more of the least frequently used words; (8) collaboration was a barely mentioned term, although the preeminence of research and the dominance of groups in knowledge is now a global trend; (9) the youngest universities tend to use more of the least frequently used words; (10) public universities emphasized individuals (i.e., students) and private universities emphasized education as a whole; and (11) the private sector has a noticeable interest in the society which contrasts with the public sector's focus on community. Research limitations/implications: Subsamples of certain regions should be more inclusive in further studies. Considering that the mean sample of MS studies was 89.6, this study used a sample more than two times larger. Although, both African (4) and Latin American (5) subsamples were not significant compared with European (94) or North American (79) subsamples. Further studies should consider a more-inclusive sampling than the QS world university ranking. Practical implications: University planning offices can use these results and the digital database to construct a global outlook on MS trends or uncommonly used words to define the purpose of their university and future course of action, embrace an overall isomorphism, or seek a distinctive strategy to differentiate their MS from others. In addition, this research can be used by strategic planning scholars to conduct regionally or nationally focused studies. Social implications: Universities' MS serve as public pronouncements of their purpose, ambition, and values. In this study, we present and analyze the contents of those purposes, in which mission-oriented universities, some of them global influencers, seek to perform in multiple levels of importance for every country (i.e., education, research, and services with both private and public sectors, and the community). Originality/value: Most of the previous studies have been restricted to national contexts and based on reduced samples with no open access digital data. In this study, we consider a wide sample of universities from Europe, North America, Asia, and Oceania. We also considered both Latin America and Africa in a strictly exploratory fashion due to sample restriction and delivered a digital open access database of MS from those universities. © 2018, OmniaScience.